Complex continuous wavelet coherence for EEG microstates detection in insight and calm meditation - Kopal, Jakub; Vyšata, Oldřich; Burian, Jan; Schätz, Martin; Procházka, Aleš; Vališ, Martin (Consciousness and cognition, 2014)
Complex continuous wavelet coherence (WTC) can be used for non-stationary signals, such as electroencephalograms. Areas of the WTC with a coherence higher than the calculated optimal threshold were obtained, and the sum of their areas was used as a criterion to differentiate between groups of experienced insight-focused meditators, calm-focused meditators and a control group. This method demonstrated the highest accuracy for the real WTC parts in the frontal region, while for the imaginary parts, the highest accuracy was shown for the frontal occipital pairs of electrodes. In the frontal area, in the broadband frequency, both types of experienced meditators demonstrated an enlargement of the increased coherence areas for the real WTC parts. For the imaginary parts unaffected by the volume conduction and global artefacts, the most significant increase occurred for the frontal occipital pair of electrodes.
Keywords: dospělí; Female; Adult; mladý dospělý; ženské pohlaví; lidé; Imagination; imaginace; Meditation; Male; Young Adult; mozková kůra; Cerebral Cortex; lidé středního věku; mužské pohlaví; meditace; elektroencefalografie; Middle Aged; Electroencephalography; Humans